On the neglected Scopoli’s name Senecio littoralis (Compositae) and its nomenclatural implications - Calvo, Joel; Sennikov, Alexander N. (Phytotaxa, 2018)
The taxonomic identity of Scopoli’s Senecio littoralis is discussed in order to support that this neglected name should be synonymized under Dittrichia viscosa. On the other hand, the name Senecio falklandicus is retrieved as the priority name for a Falkland species widely accepted in the latest years under the illegitimate name S. littoralis described by Gaudichaud-Beaupré. The Scopoli’s name S. littoralis is neotypified and a new lectotype is designated for the name S. falklandicus according to ICN 9.19(b).